Development of Microcontroller-Based SKARDIOLED (Cardiovaskular System LED) Teaching Aids in Class XI Biology - Muhammad Yusman; Adieba Warda Hayya (Universitas Negeri Padang Address: Biology Education Study Program Faculty Mathematics and Natural Science (FMIPA) Jl. Prof. Dr. Hamka Air Tawar Barat, Padang-West Sumatera-Indonesia Telp. +62751-7057420 - Fax.+62751-7058772 - Ph. +6281363229286, 2023)
Curriculum changes to independent learning are a result of developments in the Society 5.0 era and this is a challenge for educators to be able to plan student-centered learning and solutions by utilizing media in learning. So that research was carried out on the Development of SKARDIOLED Teaching Aids (LED Cardiovascular Systems) Based on Microcontrollers, the research aims to determine the development and feasibility of SKARDIOLED teaching aids. The research method uses Research and Development using a 3-D model with the Define, Design, and Develop stages, this model is adapted from the model developed by Thiagarajan, namely 4-D. Research subjects include validators and students. The validators included media experts and material experts from the Tadris Biology lecturer at IAIN Kudus and educator experts from the Biology teacher MAN 1 Kudus and students from Class XI MIPA MAN 1 Kudus with 9 students from XI MIPA 6 as a limited test and 30 students from class XI MIPA 5 as a field test. The validation results obtained a score of 100% from media experts, a score of 93.33% from material experts, and a score of 88% from educators, with the category